The use of digital technologies in the system of distance education: foreign experience and Kazakhstan (Journal of Educational Sciences, 2021)
In the process of distance education, the main role is given to digitalization, which essentially changes the methodology and algorithm in the learning process. This is especially true in the higher education system, where online courses, trainings and other innovative teaching methods are common in the practice of training. In modern conditions of obtaining knowledge and training specialists, innova- tive approaches to achieving digital literacy, mastering the key competencies of the digital economy are required. The purpose of the research in the scientific article proposed by the authors is to analyze current trends in the use of digital technologies in the system of distance education (DO); based on the study of foreign and domestic experience, to identify the pros and cons in the field of distance learning in the context of the transition to digital format.The programs and projects implemented by state bodies in the field of distance education are fo- cused on the transformation of the entire technological process of education and training. All this comes down to the training of highly qualified specialists of the innovative formation that meet the new require- ments of the digital economy.The article also notes the negative consequences of the current trend involving the distance educa- tion system. Thus, modern society will have to cope with such problems as the need to address the issues of adapting the educational system to the digital environment, the reduction of traditional employment markets instead of other areas of training, which is accompanied by the presence of ethical aspects of the use of digital technologies, the vulnerability of human rights in the digital space, the growth of cy- bercrime, and others.In response to these challenges, the tasks of organizational and legal regulation of the education system, which has switched to the distance learning mode, come to the fore. To identify problems and recommendations, a sociological survey was conducted among respondents studying in this mode be- fore, as well as the opinions of experts dealing with the optimization of the educational process in the context of the use of digital technologies were systematized.Key words: on-line education, digitalization, RK, distance learning (DL), mass open online courses( MOOCs), digital technologies of educational programs, digital literacy, information security, graduates, information and communication technologies (ICT).